Cognitive flexibility is associated with sickness resilience - Vestberg, T.; Lebedev, A. V.; Jacobsen, H. B.; Lekander, M.; Sparding, T.; Landén, M.; Maurex, L.; Ingvar, M.; Petrovic, P. (Frontiers in Psychology, 2024)
Psychological constructs related to health outcomes and well-being, such as metacognitive beliefs, have been linked to executive functions in general, and cognitive flexibility more specifically. However, such effects have previously only been discussed on a theoretical level and behavioral flexibility has most often been measured through self-report, only approximating information processing capacities. Objectively measured executive functions may be a more potent predictor of health outcomes. We set out to test whether cognitive flexibility capacity was associated with sick leave in a medium sized company. We included 111 subjects of widely different occupations and assessed their executive functions using Delis-Kaplan Executive Function System test battery (D-KEFS). To assess cognitive flexibility capacity, we included Design Fluency (DF) and Verbal Fluency (VF) and computed these into an index of cognitive flexibility (DFVF). Detailed information on sick leave for the last five years was gathered from the company. Our results showed that there was a significant negative correlation between DFVF and sick leave (rs(109)= -0.23, p=0.015) in the full group as well as in the group that had at least one day of sick leave (rs(72)= -0.25, p=0.03). The results withstood adjustment for sex, age, occupation, and several core executive functions as well as autistic and ADHD-traits. The results remained for separate analyses using DF or VF. Our main findings were conceptually replicated in a group of bipolar disorder patients. This study shows that objectively measured capacity of cognitive flexibility is associated with key health outcomes such as sick leave.